Analysis of the practice of tax risk assessment in monitoring the activities of taxpayers - Ismailov Bobir Salomovich (Genius Journals, 2023)
The article states that tax authorities can improve their ability to detect possible tax evasion, ensure fair and equitable taxation, and ultimately contribute to the overall efficiency of the tax system by improving the practice of monitoring counterparties and taxpayers' activities. In the global practice of the development trends of taxation, one can see general processes aimed at strengthening the practice of fair taxation. In addition to strengthening the stable system of attracting tax revenues to the state budget, an integral part of this process is assessing the risks of not receiving the specified amount of tax revenues in the budget, determining its reasons, and improving the work in this regard both theoretically and practically. This includes improving mechanisms for data exchange between tax authorities and other relevant institutions, introducing advanced technologies for data analysis and risk assessment, strengthening cooperation and information exchange between tax administrations at the national and international levels, as well as providing tax authorities with appropriate resources and training. may include indicates the need for participation in these processes
Keywords: tax; budget policy; budget; tax administration